The introduction of social pensions and elderly mortality: Evidence 1870-1939 - Philipp Jäger (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
The strong association between income and mortality raises the question whether more generous social security systems could improve poor people's health outcomes. Thus, in this paper, I analyze whether a major social security innovation, the introduction of social pensions targeted at poor elderly people in the late 19th-early 20th century, has reduced mortality rates of senior citizens. Therefore, I use a cross-country dataset spanning from 1870 to 1939 consisting of 13 countries of which 9 eventually implemented social pensions before World War II. Applying a difference-in-difference-in-difference as well as a regression discontinuity design, I find no evidence for a decline in elderly mortality due to the introduction of social pensions. Based on aggregate census data, I argue that social pensions have reduced elderly labor supply. The reduction is much smaller than social pension recipiency rates, though. These findings suggest that social pensions have raised elderly incomes which, however, did not translate into lower mortality. – – Der starke empirische Zusammenhang zwischen Einkommen und der Lebenserwartung wirft die Frage auf, ob großzügigere Sozialversicherungssysteme die Gesundheit ärmerer Menschen verbessern. Vor diesem Hintergrund untersucht diese Arbeit inwieweit die Einführung von Sozialrenten im späten 19./frühen 20. Jahrhunderts, die Sterblichkeitsrate älterer Menschen gesenkt hat. Um diese Frage zu beantworten, nutze ich altersspezifische Sterblichkeitsraten aus 13 Ländern, von denen, zwischen 1870 und 1939, 9 Länder Sozialrenten eingeführt haben. Unter Zuhilfenahme eines Differenzen-in-Differenzen-in-Differenzen- sowie eines Regressionsdiskontinuitäten-Ansatzes, finde ich keine Hinweise darauf, dass die Sterblichkeit aufgrund der Einführung von Sozialrenten gesunken ist. Basierend auf historischen Zensusdaten argumentiere ich zudem, dass die Einführung von Sozialrenten das Arbeitsangebot von älteren Arbeitskräften reduziert hat. Der Rückgang des Arbeitsangebots ist allerdings relativ gering verglichen mit dem Anteil der Personen, welche die Sozialrente bezogen haben. Die Ergebnisse weisen daher darauf hin, dass die Sozialrenten zwar zu höheren Einkommen geführt haben; dieser Einkommensanstieg die Sterblichkeit allerdings nicht reduziert hat.
Keywords: H55; I18; 330; pension; social security; elderly mortality